Preparation and Characterization of Biochar from New Precursor - Khudair, Douha S.; Abdul-Aziz, Yasser I. (Al-Nahrain Journal for Engineering Sciences, 2024)
The purpose of this study is to investigate the potential of biochar derived from Peganum harmala (Pgh) seeds as an adsorbent material for wastewater treatment. Biochar is a cost-efficient, ecologically friendly, and effective bio-sorbent for a wide range of pollutants in wastewater. Researchers are investigating the production of biochar from novel biomass sources. Phosphoric acid (H3PO4) was utilized in a chemical activation technique to produce biochar at various concentrations (20%, 30%, and 40%). The pyrolysis process lasted three hours at 600°C in a tube furnace with an inert nitrogen gas atmosphere. Elemental analysis, Brunauer-Emmett-Teller (BET) nitrogen adsorption, scanning electron microscopy (SEM), Fourier transform infrared spectroscopy (FTIR), energy dispersive X-ray spectroscopy (EDX), The biochar was characterized using several techniques, including elemental analysis, X-ray diffraction, Fourier transform infrared spectroscopy (FTIR), Brunauer-Emmett-Teller (BET) nitrogen adsorption, scanning electron microscopy (SEM), and energy dispersive X-ray spectroscopy (EDX). The findings demonstrate the significant potential of Pgh seed-derived biochar as an inexpensive and ecologically acceptable sorbent material. A large surface area (691.58 m2g−1) was achieved at 600◦C for three hours with 40% H3PO4 activation.